Changes to the EAEU Guideline on Good Pharmacovigilance Practices - B. K. Romanov (Безопасность и риск фармакотерапии)
By Decision No. 81 of 19.06.2022, the Council of the Eurasian Economic Commission amended the Guideline on Good Pharmacovigilance Practices of the Eurasian Economic Union (EAEU GVP Guideline), the core regulatory document on pharmacovigilance requirements for the EAEU Member States. The amendment involved all critical pharmacovigilance processes, and its consequences are yet to be assessed.The aim of the study was to analyse the changes to the EAEU GVP Guideline effective since 06.12.2022.The author summarised information on the changes made to the EAEU GVP Guideline by Decision No. 81 of the Council of the Eurasian Economic Commission of 19.06.2022 “On Amendments to the Rules of Good Pharmacovigilance Practice of the Eurasian Economic Union”. He described the differences between the old and the new versions of the EAEU GVP Guideline. Having critically reviewed the updated regulatory document, the author commented on its positive and negative aspects. The review created a starting point for further analysis of the changes to the EAEU GVP Guideline. At the time of writing, there were no other published works assessing the significance of most of the changes for the pharmaceutical industry and designated pharmacovigilance organisations in the EAEU Member States. The author assessed their significance through the prism of the recent years’ events in Russia and the world, including the COVID-19 pandemic. In connection with the amended guideline coming into force in 2022, the author suggested a transitional standstill period for both the pharmaceutical industry and designated pharmacovigilance organisations. He offered further improvements for the guideline. The article may be of practical interest to pharmacovigilance specialists, heads of pharmaceutical organisations, and employees of regulatory authorities.